2010
DOI: 10.1111/j.1365-2133.2010.09791.x
|View full text |Cite
|
Sign up to set email alerts
|

A phase IIIb, multicentre, randomized, double-blind, vehicle-controlled study of the efficacy and safety of adalimumab with and without calcipotriol/betamethasone topical treatment in patients with moderate to severe psoriasis: the BELIEVE study

Abstract: ADA + C/B resulted in more rapid and higher efficacy within the first 4 weeks; thereafter, the trend was towards a higher response with ADA monotherapy. There was no statistical difference in the PASI 75 response at week 16. Both treatment regimens were well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 20 publications
7
76
0
6
Order By: Relevance
“…In 90% of patients, no additional anti-psoriatic medication was taken during the observation time. Data on the effectiveness of adalimumab are in accordance with results of several previous studies, including the open-label STE-REO study, describing a pronounced improvement in patients with nail psoriasis treated with adalimumab (12), and the randomized, controlled BELIEVE study, which reported the effectiveness of treatment for scalp psoriasis as a secondary outcome (13). In the BELIEVE study, the mean NAPSI score at baseline was 25.3 (in this study, the mean score was 13.0), and the mean PSSI score was 16.3 (in this study, the mean score was 26.8), suggesting a more severe scalp affliction in this study (comparisons with regard to the NAP-SI score are hard to draw).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In 90% of patients, no additional anti-psoriatic medication was taken during the observation time. Data on the effectiveness of adalimumab are in accordance with results of several previous studies, including the open-label STE-REO study, describing a pronounced improvement in patients with nail psoriasis treated with adalimumab (12), and the randomized, controlled BELIEVE study, which reported the effectiveness of treatment for scalp psoriasis as a secondary outcome (13). In the BELIEVE study, the mean NAPSI score at baseline was 25.3 (in this study, the mean score was 13.0), and the mean PSSI score was 16.3 (in this study, the mean score was 26.8), suggesting a more severe scalp affliction in this study (comparisons with regard to the NAP-SI score are hard to draw).…”
Section: Discussionsupporting
confidence: 75%
“…The clinical efficacy and safety of the tumor necrosis factor (TNF) inhibitor adalimumab in patients with moderate to severe chronic plaque psoriasis have been demonstrated in several randomized, doubleblind, controlled clinical trials; however, data on the effectiveness of biologics in treating nail and scalp psoriatic lesions in routine clinical practice are scarce (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…65 % nach 20-wöchiger Therapie. In einer Studie von Thaci et al [66] Fragen zum CME-Artikel Nagelpsoriasis de ein.…”
Section: Ciclosporin a Methotrexat (Mtx)unclassified
“…com/DYZ/A2). [7][8][9][10][11][12][13][14][15][16] Most patients from the randomized clinical trials continued treatment with adalimumab in a long-term, open-label extension study. These trials were varied in their design, with broad geographic distribution and durations ranging from 12 weeks to >5 years.…”
Section: Clinical Trials and Independent Data Sources Included In Thimentioning
confidence: 99%